Creative Mathematical Thinking Ability in Creative Problem Solving Model Viewed from Gender (Universitas Negeri Semarang, 2020)
Mathematical creative thinking ability in problem solving becomes the requirement of mathematics education recently in order to find many ideas and new solution so that the issues can be resolved appropriately. This study aims to determine the effectiveness of Creative Problem Solving (CPS) learning in achieving the student’s creative mathematical thinking ability and their ability viewed from gender. This study used a mixed method design with concurrent embedded design by conducting quasi experimental design on quantitative method and Miles-Hubberman model to analyzed qualitative data. The first stage was quantitative data collection, and it was done using tests (essay). The next stage was qualitative data collection, and it was done using triangulation techniques such as tests and interviews. The study population was the grade VII SMP IT Bina Amal Semarang. Samples were grade VII Thoriq and VII Aisyah as an experimental class and grade VII Amru and VII Asma ' as the control class. Data analysis in qualitative research follows the concept given by Miles & Huberman are data reduction, data display, and conclusion drawing/verification. Analysis of quantitative research includes analysis of the achievement aspects of mathematical creative thinking abilities. Quantitative data analysis includes a normality test, homogeneity tests, completeness tests, right-side tests, and average similarity test. The result of this study shown that CPS learning model effectively improved the ability of creative thinking viewed from gender, this is indicated by the mathematical creative thinking ability of the experimental class students reaches the minimal past score, the mathematical creative thinking ability of the experimental class students is better than of the control class, the mathematical creative thinking ability of female students are better than male on elaboration and flexibility indicators, whereas the mathematical creative thinking ability of male students are better than female on fluency and originality indicators. Based on the results, it can be concluded that CPS learning can improve student’s creative thinking abilities and different achievement between male and female students.